Proceso de ASC - BIOPROSPECCION DE INGREDIENTES NATURALES EN LA AGROBIODIVERSIDAD COLOMBIANA PARA APLICACION EN LA INDUSTRIA COSMETICA (2020)
Bioprospection of yeast strains as part of the native microbiome of Coffee Mucilage, to explore as future natural ingredients for cosmetic products.